Efektivitas Sanksi Bunga dan Denda Pajak Pasca UU Cipta Kerja terhadap Kepatuhan Wajib Pajak - Nurhalizah, Nadila; Syafitri, Lili; Munandar, Aris (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
One way the government can increase prosperity in a country is through taxes. In Indonesia, the tax system has undergone various reforms to increase effectiveness and efficiency in collecting state revenue. Research aims to evaluate the effectiveness of interest sanction and tax penalty policies following the implementation of the Job Creation Law on taxpayer compliance levels at the West Ilir Tax Service Office in Palembang City. The research employs a quantitative descriptive method with data analysis using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data was collected through structured questionnaires from 100 registered taxpayers at the West Ilir Tax Service Office using slovin’s formula. The results of this study indicate that the policy of interest and tax penalty sanctions following the enactment of the Job Creation Law has successfully made tax rates more structured and proportional in improving compliance, with the majority of taxpayers (82%) stating that they are more compliant with their tax obligations after the regulatory changes were implemented. Taxpayers perceive these regulations as fairer and more in line with their financial capabilities, which in turn makes them more willing to fulfill their tax obligations.